Pemerkosaan Pada Anak - Harahap, Syaiful Akhyar; Nasution, Muhammad Arsad; Sirait, Adi Syahputra (Jurnal El-Thawalib, 2021)
The fundamental problem in this study is the Analysis of Padangsidimpuan District Court Decision No. 109/PiD.Sus/2020/PN/Psp concerning Child Rape. This study was conducted because the authors feel that the legal sanctions given by the judge to the defendant are not in accordance with what the defendant did to the victim. Sus/2020/PN/Psp and what are the reasons for the judge in imposing sanctions on the decision number 109/PiD.Sus/2020/PN/Psp.This research was conducted at the Makassar District Court. The research method used is library research method and field research method. The data obtained both primary data and secondary data from interviews and documentation were processed and analyzed qualitatively and presented descriptively.The results of the study include: the application of sanctions to the Padangsidimpuan District Court's decision Number 109/PiD.Sus/2020/PN/Psp has not provided a deterrent effect to the defendant, because from 2017-2019 data, cases of decency in children increase every year. so that the author assumes that the sanctions given by the judge to the defendant have not provided a deterrent effect to the defendant. From this case the judge has not considered the defendant's intentions and plans to commit immoral acts to the child. Even though the child will become the next generation or generation of the nation, therefore according to the author, the sanctions given by the judge are not appropriate for the defendant.